Factors related to family’s ability to care for schizophrenic patients - Dwi Indah Iswanti; Nursalam Nursalam; Rizky Fitryasari; Fery Agusman Motuho Mendrofa; Kandar Kandar (International Journal of Public Health Science (IJPHS), 2023)
Schizophrenic patients in family members makes the family helpless and unable to care for them. Patient, family, social environment, and health service factors can affect the family's ability to care for schizophrenic patients. The aims of this study are to analyze factor predictors of the family's ability to care for schizophrenic patients. This study used a correlational study design. The sample of this study is 135 schizophrenic families in the outpatient clinic of Dr. Amino Gondohutomo Regional Psychiatric Hospital with purposive sampling. The instruments in this study are the questionnaire which developed and modified from the experience caregiving instrument (ECI), inner resource scale (SAS-I), mental health inventory (MHI), Berkeley Expressivity Questionnaire, Barthel Index, caregiving tasks in caring for an adult with mental illness scale (CTiCAMIS). Data were analyzed using a multiple regression test. The result shows the family's ability to care for schizophrenic patients predicted by the variables of family resources (p-value=0.019) and social support (p-value=0.0.32). Family resources as the strongest predictor of the family's ability to care for schizophrenic patients (B=0.242). It is necessary to develop integrated family empowerment interventions that increase and activate the family's inner resources.